Success factors for business tourism destinations: evidence from Zlatibor (Serbia) - Pavluković, Vanja; Vuković, Stojan; Cimbaljević, Marija (Turizam, 2021)
Business tourism is an important and fast-growing sector in the global tourism industry. It is often positioned as a crucial part of an economic development strategy, particularly in emerging destinations, such as Serbia. As there is a growing number of destinations that recognized benefits of business tourism development, tourism professionals and destination management must be aware of key success factors for business tourism destinations, namely factors that influence the choice of host destination for a business event. Serbia has been one of the growing meeting destinations in Europe in the last decade, and Zlatibor is a desirable tourist destination in the country, with a good reputation in hosting meetings primarily in the field of medicine. This study aims to examine the success factors for business tourism destination and the attractiveness of Zlatibor for holding business events from destination stakeholders' perspective. The results could be of interest to all stakeholders in business tourism.
Keywords: business tourism; meetings industry; destination selection criteria; convention bureau; Zlatibor